Voltage tracking of bridgeless PFC cuk converter using PI controller - W. M. Utomo; N. A. A. Isa; A. A. Bakar; A. F. H. A. Gani; B. E. Prasetyo; H. Elmunsyah; Y.M.Y Buswig (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper proposes a Proportional-Integral (PI) control voltage tracking of Bridgeless Power Factor Correction (BPFC) Cuk converter.  In order to investigate the behaviour of different output voltages during overshoot, steady state and step response, P.I controller is designed to set the -42 V, -48 V, -54 V output voltages. The simulation results show that the proposed PI controller able to control the output voltage and achieve fast steady state and step response of BPFC Cuk converter.  When the value of output voltage increase, the overshoot voltage will become higher but the steady state respond will be faster. Furthermore, BPFC Cuk converter with P.I controller have low output voltage ripples.